A study on the percentage of pacing strategies in elite Asian rowers: analysis of crew, boat type, and gender - Khamros, W.; Rattanasateankij, W.; Peepathum, P.; Senakham, N.; Phongsri, K.; Mitranun, W.; Pimboon, B.; Jardsakul, P.; Suwannathat, N.; Senakham, T. (International Journal of Kinesiology & Sports Science, 2024)
Background For optimal performance, rowers should maintain a consistent rowing cadence over the entire distances. However, the rowing cadence of each category can be influenced by several factors. Understanding the rowing strategy related to these factors may help improve rowing performance.